Law Enforcement of State Losses Through Civil Proceedings: Exploration of the Role and Analysis of Alternative Options in Corruption Cases - Remigio Pereira da Cruz; Alarico Mendonca Tilma; Avelino Coelho da Silva (Universitas Ekasakti, 2024)
Corruption in Timor-Leste has become a chronic issue that harms the country's finances and economy, as well as violates the social and economic rights of the people. Efforts to recover state financial losses due to corrupt practices through civil proceedings have not been optimal, with the focus being more on criminal prosecution, which has proven to be ineffective. This research aims to examine the concept of recovering state financial losses through civil processes in Timor-Leste, identify obstacles in filing civil lawsuits, and formulate an ideal model and specific regulations for civil lawsuits in the context of recovering the proceeds of corruption. The study uses a qualitative approach by examining relevant legal documents and analyzing the judicial process and financial management in Timor-Leste. The focus of this research is on the application of civil lawsuit rules in recovering the proceeds of corruption and the challenges faced. The results show that the use of civil forfeiture can be a solution to expedite the recovery of corrupt assets through civil proceedings. The research also found obstacles in civil lawsuits, such as the ineffectiveness of criminal prosecution in reducing corruption and the need for anti-corruption legal reforms to improve the mechanism for recovering corrupted state assets. The proposed ideal model includes strengthening the role of the administrative tax and accounts court in examining the management and financial responsibility of the state, as well as placing civil lawsuits as the primary legal effort in combating corruption. This research underscores the importance of legal reforms and the implementation of civil lawsuits as the main strategy in fighting corruption in Timor-Leste. The use of civil forfeiture and asset confiscation through administrative channels is necessary to expedite the recovery of corrupt assets and reduce state financial losses.